Critical Notes on the "Tangled Threads" of Norms for Preventing and Handling Sexual Violence in the Higher Education Environment - Muammar Muammar; Iqbal Taufik (LUTUR Law Journal, 2025)
This paper aims to analyze, examine and criticize the norms of the Regulation of the Minister of Education and Culture on the Prevention and Handling of Sexual Violence which in substance still leaves a number of "tangled threads" to be resolved. The approach methods used in this paper are the statute approach, the conceptual approach, and the analytical approach. The Regulation of the Minister of Education and Culture on the Prevention and Handling of Sexual Violence, which was passed in 2022, actually aims to prevent and handle sexual violence in the university environment. However, the existence of these norms still leaves various problems that should be resolved so that the mission of the norm can be carried out effectively. These problems include, first, the nuances of contadicitio in terminis between the norm numbering and the substance that is the object of the norm. Second, the extension of terms in the norm is excessive and not in line with the true meaning of sexual violence. Third, objects (acts) that are categorized as sexual violence deviate from the proper legal concept. Fourth, it still opens gaps and opportunities for sexual violence to occur with the phrase "without the consent of the victim". Fifth, it raises the potential for a conflict of derogation principles between the lex superior derogate legi inferiori and the lex specialis derogate legi generali. Therefore, in the future, it is necessary to make revisions for the sake of improvement, so that the problem in question can be solved properly.